Advertisement Remove all ads

If X Lies in the First Quadrant and Cos X = 8 17 , Then Prove That: Cos ( π 6 + X ) + Cos ( π 4 − X ) + Cos ( 2 π 3 − X ) = ( √ 3 − 1 2 + 1 √ 2 ) 23 17 - Mathematics

Short Note

If x lies in the first quadrant and \[\cos x = \frac{8}{17}\], then prove that:

\[\cos \left( \frac{\pi}{6} + x \right) + \cos \left( \frac{\pi}{4} - x \right) + \cos \left( \frac{2\pi}{3} - x \right) = \left( \frac{\sqrt{3} - 1}{2} + \frac{1}{\sqrt{2}} \right)\frac{23}{17}\]

 

Advertisement Remove all ads

Solution

\[\text{ Given: }0 < x < \frac{\pi}{2}\]
\[\text{ Now, }\sin x = \sqrt{1 - \cos^2 x} = \sqrt{1 - \frac{64}{289}} = \frac{15}{17}\]
\[\text{ LHS }= \cos\left( \frac{\pi}{6} + x \right) + \cos\left( \frac{\pi}{4} - x \right) + \cos\left( \frac{2\pi}{3} - x \right)\]
\[ = \cos(30 + x) + \cos(45 - x) + \cos(120 - x)\]
\[ = \cos 30^\circ \cos x - \sin30^\circ \sin x + \cos 45^\circ \cos x + \sin 45^\circ \sin x + \cos120^\circ \cos x + \sin120^\circ \sin x \left\{\text{ Using formulas of }\cos(A + B)\text{ and }\cos(A - B \right\})\]
\[ = \cos x(\cos 30^\circ + \cos 45^\circ + \cos120) + \sin x( - \sin 30^\circ + \sin 45^\circ + \sin 120^\circ)\]
\[ = \frac{8}{17}\left( \frac{\sqrt{3}}{2} + \frac{1}{\sqrt{2}} - \frac{1}{2} \right) + \frac{15}{17}\left( - \frac{1}{2} + \frac{1}{\sqrt{2}} + \frac{\sqrt{3}}{2} \right) \]
\[ = \frac{8}{17}\left( \frac{\sqrt{3} - 1}{2} + \frac{1}{\sqrt{2}} \right) + \frac{15}{17}\left( \frac{\sqrt{3} - 1}{2} + \frac{1}{\sqrt{2}} \right)\]
\[ = \frac{23}{17}\left( \frac{\sqrt{3} - 1}{2} + \frac{1}{\sqrt{2}} \right) \]
 = RHS
Hence proved .

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 7 Values of Trigonometric function at sum or difference of angles
Exercise 7.1 | Q 24 | Page 20
Advertisement Remove all ads

Video TutorialsVIEW ALL [1]

Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×